Stem cells prevent long-term deterioration of renal function after renal artery revascularization in a renovascular hypertension model in rats - Nikolas Waack; Tatiana Guirao; Edgar Maquigussa; Erika Nishi; Milene Ormanji; Olinda Ykuta; Mirian Boim (Scientific Reports)
Abstract Partial stenosis of the renal artery causes renovascular hypertension (RVH) and is accompanied by chronic renal ischemia, resulting in irreversible kidney damage. Revascularization constitutes the most efficient therapy for normalizing blood pressure (BP) and has significant benefits for renal function; however, the tissue damage caused by chronic hypoxia is not fully reversed. Mesenchymal stem cells (MSCs) have produced discrete results in minimizing RVH and renal tissue and functional improvements since the obstruction persists. This study aimed to evaluate the effects of administration of MSCs in combination with renal artery revascularization in rats subjected to RVH. The following groups were evaluated: control (SHAM), hypertensive (2K-1C), hypertensive treated with MSCs (MSC), hypertensive subjected to revascularization (REV), and hypertensive subjected to revascularization and treatment with MSCs (REV + MSC). The animals were followed up for 10 weeks. The animals in the MSC group received cell infusions at the 3rd, 5th, 7th and 9th weeks. In the REV and REV + MSC groups, the clip was removed by the 6th week (revascularization), and in the REV + MSC group, MSCs infusion was performed at the 6th and 8th weeks. Tail systolic blood pressure (SBP) was measured weekly, and histological parameters and renal function were evaluated at the end of the protocol. The clipped animals developed RVH, deterioration of total renal function (50% decrease in creatinine clearance), and significant proteinuria (15x increase). Treatment with MSCs had no detectable beneficial effects on kidney function or SBP. REV resulted in normalization of BP and a significant but partial reduction in proteinuria (80% vs. 2K-1C), but areas with renal fibrosis persisted. The combination of the two treatments was effective at normalizing all renal parameters as well as reversing proteinuria, reducing the number of ischemic glomeruli and atrophic tubules, indicating an improvement of the renal parenchyma. The results suggest that therapy with MSCs associated with revascularization can potentially help in the full recovery of renal function in the long term in patients with RVH.